1998
DOI: 10.1177/107769909807500118
|View full text |Cite
|
Sign up to set email alerts
|

Of Horse Race and Policy Issues: A Study of Gender in Coverage of a Gubernatorial Election by two Major Metropolitan Newspapers

Abstract: This study of news coverage of a gubernatorial race suggests (1) gender may be a larger factor in selection of policy stories than in selection of horse race stories; (2) coverage of the horse race, particularly news coverage of advertising strategy, appears to have greater impact on the outcome of the election than coverage of policy issues; (3) a woman will be more successful in a political race if she presents herself as a man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
2
11
1
Order By: Relevance
“…This finding counters previous studies that found in most elections involving an African American or female candidate, the media often focused on a Black candidate's race (Caliendo & McIlwain, 2006;Citrin et al, 1990;McDermott, 1998;Sigelman et al, 1995) or a female candidate's gender (Kahn, 1994;Kahn & Goldenberg, 1991;Scharrer, 2002;Serini et al, 1998). This finding is significant in that it suggests media coverage might also be guided by the conventions of what makes news (i.e., novelty timeliness, proximity, etc.)…”
Section: Summary and Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…This finding counters previous studies that found in most elections involving an African American or female candidate, the media often focused on a Black candidate's race (Caliendo & McIlwain, 2006;Citrin et al, 1990;McDermott, 1998;Sigelman et al, 1995) or a female candidate's gender (Kahn, 1994;Kahn & Goldenberg, 1991;Scharrer, 2002;Serini et al, 1998). This finding is significant in that it suggests media coverage might also be guided by the conventions of what makes news (i.e., novelty timeliness, proximity, etc.)…”
Section: Summary and Discussioncontrasting
confidence: 81%
“…This falls in line with previous research showing that by focusing on gender, the media may hurt female candidates at the polls as it often restricts voters' perception of them (Bystrom et al, 2001;Devitt, 2002;Serini et al, 1998;Kahn, 1994;Kahn & Goldenberg, 1991;Koch, 1999;Norris, 1997). Scharrer (2002), for example, noted in comparing how people perceived Clinton and former New York City Mayor Rudy Giuliani in their respective bids for political office that:…”
Section: Summary and Discussionsupporting
confidence: 61%
See 3 more Smart Citations